Equity initiatives for sustainable development: A comparative study of affirmative action in the USA and India - Neeraj Pant; Alka Sharma (Social Sciences and Humanities Open)
The primary objective of this paper is to analyze the affirmative action programs in India and the USA, exploring their similarities, differences, structures, and outcomes. Despite formal and structural disparities, both nations share a similar intent in implementing affirmative action policies. Over the years, affirmative action initiatives in both India and the USA have sparked intense controversy and ongoing discussions. This research aims to establish meaningful comparisons between the two affirmative action systems, evaluate their respective strengths, and offer recommendations for an improved system suitable for contemporary India. The paper adopts a theoretical approach in its analysis and reaches conclusions about which system might be more effective for India in the present context through a comparative assessment of the existing models. The voluntarily actions of the United States with broad dimensions of its coverage with special reference to the women representation is found as a new idea to relook present affirmation action programmes of India.